Early Career Researchers between Predatory Publishing and Academic Excellence: The Views and Behaviours of the Millennials - David Nicholas; Eti Herman; Anthony Watkinson; Jie Xu; Abdullah Abrizah; Blanca Rodríguez-Bravo; Cherifa Boukacem-Zeghmouri; Tatiana Polezhaeva; Marzena Świgon (Foresight and STI Governance)
The paper draws on evidence of predatory publishing obtained from the 4 year-long Harbingers research study of the changing scholarly communication attitudes and behaviour of early career researchers (ECRs). The project featured longitudinal interviews for its first 3 years with 116 ECRs researching science and social sciences who came from China, France, Malaysia, Poland, Spain, UK and USA. The interview data provided the building blocks for a questionnaire survey in the 4th year, which obtained 1600 responses from a global audience, which included arts and humanities ECRs and those from Russia. These studies investigated predatory publishing as part of general questioning about scholarly communications, in other words, in context. The main finding from the interview study were: 1) ECRs generally do not publish in predatory journals; 2) they only allude to them lightly and mainly in the context of open access publishing; 3) they no longer acquaint all open access publishing with predatory journals. The questionnaire found that, as in the case of the interviews, complaints that open access is low quality publishing are diminishing, however, this positivity has been partly offset by increased concerns about the dangers of predatory journals.